Acute Phase Peyronie's Disease Management with Traction Device: A Nonrandomized Prospective Controlled Trial with Ultrasound Correlation. (1st February 2014) - Martínez‐Salamanca, Juan I.; Egui, Alejandra; Moncada, Ignacio; Minaya, Javier; Ballesteros, Claudio Martínez; del Portillo, Luis; Sola, Ignacio; Carballido, Joaquín
Abstract: Introduction: Outcome data of penile traction therapy (PTT) for the acute phase (AP) of Peyronie's disease (PD) have not been specifically studied. Aim: The aim of this study was to assess the effectiveness of a penile extender device for the treatment of patients with AP of PD. Methods: A total of 55 patients underwent PTT for 6 months and were compared with 41 patients with AP of PD who did not receive active treatment ("no intervention group" [NIG]). Main Outcomes Measures: Pre‐ and posttreatment variables included degree of curvature, penile length and girth, pain by 0–10 cm visual analog scale (VAS), erectile function (EF) domain of the International Index of Erectile Function questionnaire, Erection Hardness Scale, Sexual Encounter Profile 2 question, and penile sonographic evaluation (only patients in the intervention group). Results: The mean curvature decreased from 33° at baseline to 15° at 6 months and 13° at 9 months with a mean decrease 20° ( P < 0.05) in the PTT group. VAS score for pain decreased from 5.5 to 2.5 after 6 months ( P < 0.05). EF and erection hardness also improved significantly. The percentage of patients who were not able to achieve penetration decreased from 62% to 20% ( P < 0.03). In the NIG, deformity increased significantly, stretched flaccid penile length decreased, VAS score for pain increased, and EF and erection hardness worsened. PTT was associated with the disappearance of sonographic plaques in 48% of patients. Furthermore, the need for surgery was reduced in 40% of patients who would otherwise have been candidates for surgery and simplified the complexity of the surgical procedure (from grafting to plication) in one out of every three patients. Conclusions: PTT seems an effective treatment for the AP of PD in terms of pain reduction, penile curvature decrease, and improvement in sexual function.